SISTEM CARI AMBULANCE MENGGUNAKAN ALGORITMA A-STAR - Febriansyah, Febriansyah; Aziz, Asmawaty; Rasyid, Kurniawan Harun (Aliansi Dosen Perguruan Tinggi Swasta Indonesia (Adpertisi), 2024)
Ambulance Search System Using the A* (Star) Algorithm, Yanti Feronika, Ambulance is a transportation unit provided by the hospital. One of them is in the city of Makassar which provides ambulance services. the journey to the hospital. Despite the rapid development of technology, there are several main problems that people often complain about today, namely when evacuating emergency patients using ambulances, but the issue of distance/route is still a problem for everyone who wants to visit the hospital. With the development of existing technology, a method for determining the closest route was introduced. Currently it has been widely applied in various navigation applications. The process of calculating the closest route is the process of finding the smallest of a route from the initial node to the destination node in a network. This study uses the A* algorithm to determine the closest route. After the calculation process is carried out using the A-Star algorithm formula with a different route notation, the results of the calculation of the closest route from the starting point to the destination point have a value on the route with the notation